Evidence on the Dark Side of Internal Capital Markets - Ozbas, Oguzhan; Scharfstein, David S. (Review of Financial Studies, 2010)
[This article documents differences between the Q-sensitivity of investment of stand-alone firms and unrelated segments of conglomerate firms. Unrelated segments exhibit lower Q-sensitivity of investment than stand-alone firms. This fact is driven by unrelated segments of conglomerate firms that tend to invest less than stand-alone firms in high-Q industries. This finding is robust to matching on industry, year, size, age, and profitability. The differences are more pronounced in conglomerates in which top management has small ownership stakes, suggesting that agency problems explain the investment behavior of conglomerates.]